Osteogenesis Imperfecta : A Case Report - Hastopraja, Ressy; Nasution, Melati Silvanni (TALENTA Publisher, Universitas Sumatera Utara, 2022)
ABSTRACT Background: Osteogenesis imperfecta (OI) comprises a heterogeneous group of diseases characterized by susceptibility to bone fractures with variable severity and, in most cases, with presumed or proven defects in collagen type I biosynthesis and an estimated prevalence of 1/15,000 births. Management is multidisciplinary involving mainly surgery, physiotherapy, and rehabilitation Case Presentation: A young woman the age of 19 years old came to the Endocrine Polyclinic of H. Adam Malik Hospital, with a complaint of a fracture of the arm and left thigh for 4 years due to a slip. SinceÂ a small age, there was difficulty walking due to the twisted bones of the limbs, and surgery was performed. The conclusion of X-ray of right and left femur bones according to the description of osteogenesis imperfecta accompanied by a picture of fracture and osteomalasia and the conclusion of the whole body scan: pathological picture in the bones can be caused by osteogenesis imperfecta. Conclusion:Â A young woman the age of 19 years old has been reported may have OI type 1, management is multidisciplinary involving mainly surgery, physiotherapy, and rehabilitation.